2020
DOI: 10.1098/rstb.2019.0604
|View full text |Cite
|
Sign up to set email alerts
|

The study of host–microbiome (co)evolution across levels of selection

Abstract: Microorganismal diversity can be explained in large part by selection imposed from both the abiotic and biotic environments, including—in the case of host-associated microbiomes—interactions with eukaryotes. As such, the diversity of host-associated microbiomes can be usefully studied across a variety of scales: within a single host over time, among host genotypes within a population, between populations and among host species. A plethora of recent studies across these scales and across diverse systems are: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 84 publications
(93 reference statements)
2
64
0
2
Order By: Relevance
“…We are aware that the sample sizes for our study are small and unequal numbers of samples were included per group, therefore any conclusions about differences between the microbiota of ruminant species should be drawn cautiously. However, our data are supportive of the hypothesis that there are host species-specific rumen microbiota at the strain and species level, potentially due to the co-evolution of the microbiome and host 37 , but that these differences do not necessarily translate into large differences in the types of CAZymes expressed. While we found that there were significant differences between the abundances of CAZymes and KEGG orthologs between ruminant species, most CAZymes and KEGG orthologs were present in all ruminant species.…”
Section: Discussionsupporting
confidence: 79%
“…We are aware that the sample sizes for our study are small and unequal numbers of samples were included per group, therefore any conclusions about differences between the microbiota of ruminant species should be drawn cautiously. However, our data are supportive of the hypothesis that there are host species-specific rumen microbiota at the strain and species level, potentially due to the co-evolution of the microbiome and host 37 , but that these differences do not necessarily translate into large differences in the types of CAZymes expressed. While we found that there were significant differences between the abundances of CAZymes and KEGG orthologs between ruminant species, most CAZymes and KEGG orthologs were present in all ruminant species.…”
Section: Discussionsupporting
confidence: 79%
“…Overall, our study suggests that mutualistic microbes may act like facilitator species during ecological succession, promoting the establishment of their hosts while maintaining separate fitness interests that maintain selection for antagonistic loci. Although holobiont theory has sometimes been used to characterize plant-microbe interactions (Hassani et al 2018), the mismatches we detect between host and symbiont fitness interests suggest that individual populations of hosts and symbionts are more appropriate units of selection in this system (Koskella and Bergelson 2020).…”
Section: Exploitation In Mutualismmentioning
confidence: 91%
“…As in the case of the sterile newborns, there is there a “founder effect” involving the neighbor bacterial populations from kin individuals. This core phyla microbiota in mammals can diverge depending on the mammals’ evolution and diversification ( Moeller and Sanders, 2020 ), mostly at the lower taxonomic ranks where particular types of bacteria tend to be associated with mammalian lineages, which implies a host niche-microbiota coevolution, probably based on differences in the intestinal chemosphere, including adaptation to diet and the local immune response ( Shapira, 2016 ; Nishida and Ochman, 2018 ; Koskella and Bergelson, 2020 ). The need for maintaining the basic intestinal microbial niche under differing diets might have influenced the enlargement (possible niche construction) of parts of the gut (as foregut fermenters) to ensure long-term microbe-food interaction ( Ley et al, 2008a , b ).…”
Section: Bacterial Niche Construction In Higher Speciesmentioning
confidence: 99%